Marketing para la empresa Lavamax en la ciudad de Babahoyo. - Guerra Zuñiga, Rominna Mariella (2022)
This study shows that digital marketing can contribute to improving the positioning of LAVAMAX in the city of Babahoyo, a company with activities related to the washing of garments from different households in the city, but despite the opportunities that At the present time, technology is provided, they still use traditional marketing in their advertising, which has caused the company to not have potential and loyal customers. To carry out the collection of data on the causes of the problem, a methodology of a described nature was applied, through the use of the survey technique aimed at owners and employees. This led to the conclusion that there is still a lack of knowledge about the proper management of digital strategies for the proper use of marketing, and that it is advisable for the staff to be immersed in this type of very useful issues when making decisions regarding the forms to position itself in the local market. Viable alternatives must be sought that ensure the profitability of the business and that it emerges over time and in the spaces where its presence has been defined, according to current needs. Therefore, the objective of this research focuses on identifying the incidence of digital marketing for the company LAVAMAX in the city of Babahoyo.